Clinicopathological and Immunohistochemical Characteristics of Esophageal Carcinosarcoma - SANO, Akihiko; SAKURAI, Shinji; SANO, Takaaki; HOSOYA, Yoshinori; ENOMOTO, Takehiko; KANDA, Tatsuo; AJIOKA, Yoichi; OYAMA, Tetsunari; KUWANO, Hiroyuki; KATO, Hiroyuki; SAKAI, Makoto; TANAKA, Naritaka; et al. (Anticancer research, 2009)
Background: Esophageal carcinosarcoma is a very rare neoplasm and its clinicopathological characteristics and the prognostic factors that influence the clinical outcome of the patient remain a matter of controversy. Patients and Methods: Twenty patients with esophageal carcinosarcoma were referred to our institutions. Tissue blocks were reviewed and sections containing both carcinomatous and sarcomatous components were stained for epithelial and mesenchymal markers and a proliferating cell marker. The prognosis of the esophageal carcinosarcoma patients was compared with 142 cases of esophageal squamous cell carcinoma. Results: In the carcinomatous component, the expression of cytokeratin, epithelial membrane antigen, vimentin, smooth muscle actin, and S100 were detected in 20, 20, 1, 1, and 1 case, respectively, whereas in the sarcomatous component, expression of these were detected in 4, 2, 18, 15, and 3 cases, respectively. The Ki-67 labeling index of carcinomatous and sarcomatous components was 35.5% and 41.8%, respectively. The 5-year survival rate was not statistically different between squamous cell carcinoma and carcinosarcoma (p=0.219). However, for T1 cases only, carcinosarcoma patients had statistically poorer prognosis than did squamous cell carcinoma patients (p=0.008). Conclusion: The sarcomatous component shows various histological and immunohisto-chemical forms. In comparison with squamous cell carcinoma patients, carcinosarcoma patients had poorer prognosis amongst the T1 cases. For the treatment of esophageal carcinosarcoma, it is important to monitor lymph nodes and be watchful for hematogenous metastasis, as in cases of esophageal squamous cell carcinoma.